1967
DOI: 10.1111/j.1151-2916.1967.tb15096.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the System MgO‐FeO‐Fe2O3: The 1300°C Isothermal Section and Extrapolations to Other Temperatures

Abstract: The 13OO0C isotherm of the system MgO-FeOFe203 was studied thermogravimetrically under conditions of controlled fugacity of oxygen. The magnesioferrite solid solutions that coexist in equilibrium with magnesiowiistite solid solutions have a cation to anion ratio experimentally indistinguishable, in the present study, from 0.750. Curves are presented expressing the change in composition of coexisting magnesioferrite and magnesiowiistite phases as a function of temperature and oxygen fugacity. These curves for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1974
1974
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…In the MgO-FeO-Fe 2 O 3 system, Speidel has shown that magnesiowustite or magnesioferrite spinel may exist depending on the oxygen potential. [12] The SEM results of this study showed that under p o 2 ϭ 10 Ϫ6 and 3.73 ϫ 10 -4 atm, a magnesioferrite spinel formed at the slag-refractory interface and behind this spinel layer was a magnesiowustite solid solution inside the refractory. Under p o 2 ϭ 10 Ϫ8 atm, only a magnesiowustite solid solution layer was observed at the interface.…”
Section: B Reaction Layers At the Interfacementioning
confidence: 58%
“…In the MgO-FeO-Fe 2 O 3 system, Speidel has shown that magnesiowustite or magnesioferrite spinel may exist depending on the oxygen potential. [12] The SEM results of this study showed that under p o 2 ϭ 10 Ϫ6 and 3.73 ϫ 10 -4 atm, a magnesioferrite spinel formed at the slag-refractory interface and behind this spinel layer was a magnesiowustite solid solution inside the refractory. Under p o 2 ϭ 10 Ϫ8 atm, only a magnesiowustite solid solution layer was observed at the interface.…”
Section: B Reaction Layers At the Interfacementioning
confidence: 58%
“…The phase diagram of the MgO -FeO -Fe 2 O 3 system at 1300 ºC (Speidel, 1967) indicates that ferropericlase is the unique stable phase under the experimental conditions in the present study. However, our samples contained a minor amount of magnesioferrite, even in synthesized samples.…”
Section: Synthetic Productsmentioning
confidence: 50%
“…Moreover, as the Mn ions in the present experimental condition are permanently divalent because f O 2 at the MnO -Mn 3 O 4 buffer is much higher (Huebner, 1971), the redox reaction of Mn would not have affected the experimental results. A 100 mg pellet was made and placed into a Pt -cup and heated at 1300 °C within an atmosphere -controlled furnace for 48 h. The justification for choosing this temperature condition is that the phase diagram of the MgO -FeO -Fe 2 O 3 system has previously only been established at this temperature condition (Speidel, 1967). The oxygen fugacity (log f O 2 ) was controlled at −7, −9, −11, using a mixed gas of H 2 and CO 2 .…”
Section: Sample Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, however, the compositions of Fe x O-MgO solid solutions were determined only after preparations at 1573 K, and are superimposed on the isothermal section of the ternary system of stoichiometric FeO, Fe 2 O 3 and MgO at 1573 K, 14) shown in Fig. 4.…”
Section: Discussionmentioning
confidence: 99%